Gold nanoparticles supported on magnesium oxide for CO oxidation; Nanoscale Research Letters; Vol. 6, Art. 435 - Carabineiro S. A. C.; Bogdanchikova N.; Pestryakov A. N. Aleksey Nikolaevich; Tavares P. B.; Fernandes L. S. G.; Figueiredo J. L. (2011, 2011)
Proceedings 11th International Conference (TNT2010) Trends in NanoTechnology